Antibacterial Activity of Flavonoids from Ethyl Acetate Extract of Milk Banana Peel (Musa x paradisiaca L.) - Wiwik Susanah Rita; Ida Ayu Raka Astiti Asih; I Made Dira Swantara; Ni Luh Yuli Damayanti (Bogor Agricultural University, Indonesia, 2021)
Infectious diseases caused by Staphylococcus aureus and Escherichia coli can be treated by milk banana peels (Musa × paradisiaca L.). This study aims to reveal the antibacterial activity of milk banana peel ethyl acetate extract against Staphylococcus aureus and Escherichia coli, and to identify their active compounds. Extraction was conducted by maceration at room temperature, followed by partition. Separation was carried out by column chromatography with mobile phase of chloroform: ethyl acetate (7.5:2.5) and stationary phase of silica gel 60. Antibacterial assay was performed by well diffusion method and identification of active compounds was analyzed by UV-Vis spectrophotometry and LC-MS/MS. Extraction of the peel powder produced methanol extract, partition of the methanol extract resulted n-hexane, ethyl acetate, n-butanol, and water fractions. Antibacterial activity assay shows that ethyl acetate extract was the most active to inhibit the growth of both bacteria. Separation with column chromatography resulted 5 fractions. Identification of the most active fraction with UV-Vis showed that the isolate gave maximum absorption at λ 339.00 nm (band I) and λ 262.00 nm (band II) which were thought to be flavonol (3-OH substituted). Analysis with LC-MS/MS shows that the most active fraction contained 3-methacrylate flavonols and 3-(furan- 2yl) acrylate flavonols.